1998
DOI: 10.1029/97jb02540
|View full text |Cite
|
Sign up to set email alerts
|

Compaction‐driven evolution of porosity and permeability in natural mudstones: An experimental study

Abstract: Abstract. This paper describes a series of experiments designed to investigate the influence of litho!ogy on the compactional loss of porosity and permeability in mudstones. Two intact samples of London Clay with clay fractions of 40% and 67% were compacted to 33 MPa effective stress. Clay fraction, permeability, porosity, pore size distribution, and specific surface area were measured and their evolution was monitored throughout the compaction process. Electron microscopy was combined with mercury porosimetry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
189
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 208 publications
(198 citation statements)
references
References 33 publications
8
189
1
Order By: Relevance
“…Many researchers have shown that the permeability of shale decreases with externally applied stress (Dewhurst et al, 1999a;Dewhurst et al, 1999b;Katsube, 2000;Katsube et al, 1996a;Katsube et al, 1998;Kwon et al, 2001;Neuzil et al, 1984) and decreased porosity (Dewhurst et al, 1998;Schloemer and Kloss, 1997). A range of non-linear relationships have been proposed between permeability, porosity, and pressure in shale and mudstones, including exponential and power laws (Dewhurst et al, 1999a;Katsube et al, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers have shown that the permeability of shale decreases with externally applied stress (Dewhurst et al, 1999a;Dewhurst et al, 1999b;Katsube, 2000;Katsube et al, 1996a;Katsube et al, 1998;Kwon et al, 2001;Neuzil et al, 1984) and decreased porosity (Dewhurst et al, 1998;Schloemer and Kloss, 1997). A range of non-linear relationships have been proposed between permeability, porosity, and pressure in shale and mudstones, including exponential and power laws (Dewhurst et al, 1999a;Katsube et al, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…Admittedly, establishing acceptable criteria from which the compactional parameters of a firmground might be derived is an all but impossible task. In addition to the aforementioned parameters, organic content, grain sorting, grain shape, and initial pore pressure undoubtedly have a notable effect on the kinetics of the compaction process (Krumbein 1959;Hoyt and Henry 1964;Tokunaga et al 1994;Dewherst and Aplin 1998).…”
Section: The Glossifungites Ichnofaciesmentioning
confidence: 99%
“…In fact, the depth required varies with sediment texture (Fig. 7A,B), initial pore-water content, sedimentation rate, and length of time that the substrate was buried (Dewherst and Aplin 1998).…”
Section: Stratigraphic Significancementioning
confidence: 99%
“…Most of the observed variation in permeability of shale formations can be attributed to porosity variations [15,[21][22][23][24][25][26][27], grain size and pore size distributions [15,23,[25][26][27][28]. Furthermore, high anisotropy ratios observed in apparently homogeneous aquifers are caused to a lesser degree by orientation but caused mainly by micro-stratification [29].…”
Section: Introductionmentioning
confidence: 97%